The Recording and Management of Indigenous Lands and Title: Is Reform Required? - Stephenson, Margaret; Tehan, M. (2015)
Systems for assessing and recording indigenous lands are critical to the continued recognition and enforcement of indigenous titles and for the effective management of indigenous titles. With the increasing number of native title determinations in Australia it is timely to review the systems of land administration that capture and manage indigenous lands and consider if reforms to these systems are required. Indigenous land holdings in Australia are reviewed with a focus on the recording and registration of such systems. This article questions whether the current system for recording native title in Australia is adequate and whether a search for a more appropriate title recording system should be undertaken.